Mengurangi Antrean pada Stasiun Pengisian Bahan Bakar Umum dengan Pendekatan Simulasi Menggunakan ProModel - Mirna Lusiani; Anie Belita (Universitas Bunda Mulia, 2019)
The gas station has become an important facility for the public, especially for people in large cities such as Jakarta. This condition was caused by increasing demand from year to year. The number of facilities has less number than the customer that came, which could cause queueing in the station. This research was made with the purpose to reduce the number of the queue and increase the number of customers serviced at the gas station. This research located on one of the gas stations in Jakarta at 16.00-18.00 from Monday to Friday. The data used for this research is primary data which was observed directly by the researcher. The data used for this research are the number of customers arrived and service time. Data analysis is using discrete-event simulation with ProModel software. The conclusion of this research is the actual system has a relatively high number of queueing customer which also affect the reduced number of customers that was served. Improvement model was created by decreasing the service time by 10% with the average number of queues by 4 customers for Pertalite and 4customers for Premium. Scenario model is also designed as a proposal by using customer migration scenario from Premium to Pertalite by 30%, 60%, and 100%. The proposed system for the first scenario is by decreasing the service time by 20% with the average number of queues by 8 customers for Pertalite and 1 customer for Premium. For the second scenario is by modifying the queueing system and decreasing the service time by 10% with the average number of queues by 8 customers for Pertalite and 7 customers for Premium. For the third scenario is by opening a new server for Pertalite with the average number of queues by 5 customers.